2017
DOI: 10.1037/pas0000397
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Edinburgh Postnatal Depression Scale in a population-based sample.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Copyright and reuse: City Research Online aims to make research outputs of City, University of London available to a wider audience. Copyright and Moral Rights remain with the author(s) and/or copyright holders. URLs from City Research Online may be freely distributed and linked to. City Research Online: http://openaccess.city.ac.uk/ publications@city.ac.uk Permanent repository link: City Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
67
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 59 publications
(108 reference statements)
12
67
1
9
Order By: Relevance
“…Our findings are most consistent with the results in a study of Italian women (measured 2–3 days postpartum) identified by EFA with oblique rotation (Petrozzi and Gagliardi 2013) and a population-based study of women living in southwest England (measured at 18 and 32 weeks gestation, and 8 weeks and 8 months postpartum) identified by EFA with oblique rotation and CFA with maximum likelihood estimation (Coates et al 2016), both suggesting a three-factor structure including depression (items 7–10), anxiety (items 3–6), and anhedonia (items 1–2). Another study conducted via an internet survey measured at approximately 6.5 months postpartum also found a similar three-factor structure (items 7–10 for depression; items 3–5 for anxiety; items 1–2 for anhedonia) by EFA with direct quartimin rotation (Tuohy and McVey 2008).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings are most consistent with the results in a study of Italian women (measured 2–3 days postpartum) identified by EFA with oblique rotation (Petrozzi and Gagliardi 2013) and a population-based study of women living in southwest England (measured at 18 and 32 weeks gestation, and 8 weeks and 8 months postpartum) identified by EFA with oblique rotation and CFA with maximum likelihood estimation (Coates et al 2016), both suggesting a three-factor structure including depression (items 7–10), anxiety (items 3–6), and anhedonia (items 1–2). Another study conducted via an internet survey measured at approximately 6.5 months postpartum also found a similar three-factor structure (items 7–10 for depression; items 3–5 for anxiety; items 1–2 for anhedonia) by EFA with direct quartimin rotation (Tuohy and McVey 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, a three-factor model consisting of item clusters corresponding to postpartum symptoms including depressed mood, anhedonia, and anxiety provided the best fit, similar to those reported in Tuohy & McVey (Tuohy and McVey 2008), Petrozzi & Gagliardi (Petrozzi and Gagliardi 2013), and Coates et al (Coates et al 2016). In our ethnically mixed sample, the groupings differed slightly for the Hispanic subgroup compared to the African American or non-Hispanic White subgroups by one item (overwhelmed) that clustered with anxiety-type items in the former rather than depression-type items in the African Americans and Whites.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations